PENGARUH TINGKAT PERPUTARAN KAS, KOMPOSISI PENDANAAN, UMUR OPERASIONAL, DAN TINGKAT PERTUMBUHAN JUMLAH NASABAH PADA PROFITABILITAS BANK PERKREDITAN RAKYAT DI KABUPATEN BADUNG - Wahyuni, Ni Luh Oka; Putra, I Wayan (E-Jurnal Akuntansi, 2012)
This study aimed to determine the effect of cash turnover, the composition of funding, operational lifespan, and the rate of growth of the number of customers on the profitability of BPR in Badung. The population was rural banks in Badung. Samples were taken by purposive sampling which amounted to 12 RBs. This study uses data analysis techniques of multiple linear regression. The results showed turnover of cash and funding composition positively, negatively affect operational life, and the rate of growth of the number of customers had no effect on profitability. Suggestions for further research can add other independent variables that can be used to measure profitability Keywords : cash, funding composition, customers, profitability, operational lifespan